2017
DOI: 10.20960/nh.1311
|View full text |Cite
|
Sign up to set email alerts
|

Síntomas depresivos y niveles séricos de ácidos grasos poliinsaturados omega-3 y omega-6 en universitarios del norte de México

Abstract: Our results did not confirm the relationship of serum levels of PUFA omega-3 and omega-6/omega-3 ratio with depressive symptoms; the negative correlation of serum ALA with depressive symptoms remains to be confirmed in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This vitamin acts jointly with omega-3s, which participate in the synthesis of neurotransmitters and regulation of the circadian rhythm, among other functions [20,48]. However, despite these data, the results of studies that observed fish consumption with depressive symptoms are not conclusive [49].…”
Section: Discussionmentioning
confidence: 98%
“…This vitamin acts jointly with omega-3s, which participate in the synthesis of neurotransmitters and regulation of the circadian rhythm, among other functions [20,48]. However, despite these data, the results of studies that observed fish consumption with depressive symptoms are not conclusive [49].…”
Section: Discussionmentioning
confidence: 98%
“…The content of EPA+DHA for every 100 g of product of F3 was 142.6 mg, and so one serving of 30 g of tortilla chips would provide 42.8 mg of both fatty acids, amount which equals 17.1% of the daily intake recommended by the WHO/FAO of 250 mg per day (Vargas et al, 2018). According to Kaur, Chugh, and Gupta (2014), fish and fish oil are the richest sources of EPA, whether saltwater or freshwater fish, whereas DHA is not only found in reddish-brown algae, but also in fish oil, and therefore, an intake of up to two or three times a week of fish has been recommended (Nguyen, Malau-Aduli, Cavalieri, Nichols, & Malau-Aduli, 2019).…”
Section: Content Of Fatty Acidsmentioning
confidence: 99%
“…The high biological value protein and n-3 PUFA (EPA and DHA) are both considered beneficial for good health. The former, because it is composed of essential amino acids, helping increase muscular mass (Ruiz-Margáin et al, 2018), while n-3 fatty acids confer anti-inflammatory and antiarrhythmogenic properties, preventing heart diseases and type 2 diabetes mellitus (González, Rodríguez, & Gómez, 2013), and due to these properties, the World Health Organization and the United Nations Food and Agriculture Organization (OMS/FAO) recommend a daily intake of 250 mg of EPA and DHA (Vargas, Terrazas-Medina, Leyva-López, Peralta-Peña, & Cupu-Uicab, 2018). DHA is a fatty acid that has produced great interest, since it is essential for the development of the central nervous system and the retina during embryonic development, as well as being important throughout life for its neuroprotective function; it is a fatty acid found only in aquatic animals (Echeverría, Valenzuela, Hernandez-Rodas, & Valenzuela, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies on the association of n-6/n-3 ratio and depression are also controversial. Some cross-sectional or longitudinal studies suggested a positive association ( 18 , 34–36 ), whereas several other studies reported a negative association ( 37 ) or no association ( 25 , 38 ).…”
Section: Introductionmentioning
confidence: 99%